Identification of harmonic sources in smart grid using systematic feature extraction from non-active powers - Joga, S. Ramana Kumar; Sinha, Pampa; Paul, Kaushik; Sahoo, Satyabrata; Pani, Samita Rani; Dei, Geetanjali; Ustun, Taha Selim (Frontiers in Smart Grids, 2024)
The paper introduces a novel method for identifying the location of harmonicgenerating sources in smartgrids. The method utilizes a Dual-Tree Complex Wavelet Transform (DTCWT) of voltage and current signals measured at a specific point in the network. By applying DTCWT Transform, the signals are decomposed, and three non-active power quantities are extracted to represent the harmonic components within the system exclusively. These chosen nonactive power quantities serve as indicators of the presence of harmonics in the system. Through analysis and comparison of these quantities, the method enables determining the precise location of the dominant harmonic generating source. This information is valuable for effectively addressing and mitigating harmonic issues in the network. Leveraging DTCWT and focusing on non-active power quantities provides a valuable tool for power system engineers and operators to diagnose and mitigate harmonic issues, ultimately improving power quality and system performance. This study presents a new feature extraction method to compute Non-active power quantities based on DTCWT due to its shift-invariant property.